Universal Healthcare: Evaluating the Feasibility and Impact of Implementing Universal Health Coverage Worldwide - Azam, Muhammad; Soomro, Imtiaz Ali; Siddiqui, Sobia Naseem; Zainullah; Shahzad, Munawar; Khalid, Afshan (Indus Journal of Bioscience Research, 2025)
Universal health coverage, widely considered a basic human right, is a health system that ensures all people have access to necessary medical services without any financial barriers. The global discussion on UHC has gained momentum as countries strive to enhance health outcomes, reduce health inequities, and promote general social well-being. The implementation of UHC across the globe would require careful assessment of some of the major factors, including economic costs, healthcare infrastructure, political commitment, and availability of healthcare professionals. For UHC to work, a holistic approach is necessary-one that deals with various health challenges, integrates existing healthcare systems, and makes sure that services remain affordable and accessible to all populations. There are many examples of successful models of UHC that exist in Sweden, Canada, and Japan, among others. Such models have minimized health disparities, increased access to essential healthcare, and improved the population health outcome. There is still resistance to UHC expansion due to political and resource-related constraints and lack of financial support. More recently, the addition of electronic health records and telemedicine has been seen as an essential enabler to expand healthcare access and improve quality-of-service delivery. Though challenges abound, it is apparent that UHC can be attained with concerted global effort, effective funding mechanisms, and strong political will at national and international levels. UHC in the long run can definitely be a factor to improve the health equity situation of the whole world. On the one hand, it could bridge the rich and poor nations with the service delivery of health without causing the individual financial burdens.